Sleep within the NBA bubble. The impact of COVID on sleep & mental health - Bird, S. P.; Singh, M.; Charest, J.; Huyghe, T.; Calleja-Gonzalez, J. (British Journal of Sports Medicine, 2021)
A significant consideration by the performance staff heading into the NBA Bubble was the potential accumulative increase in player stress and anxiety associated with adhering to the daily NBA Coronavirus disease (COVID-19) protocols, environmental transition into the Bubble (quarantine and isolation), coupled with training and competition demands. The impact of such cumulative stress and anxiety negatively affects players mental health, resulting in significant sleep-related issues with detrimental effects on player health, recovery and performance. The National Basketball Players Association (NBPA) highlighted that the uncertainty of the situation the impact of COVID-19 on the players and staff, likely to result in a range of emotions such as "anxiety, fear, uncertainty, confusion, hypervigilance, depression, an increased sense of vulnerability, boredom, and a heightened awareness of the needs for self-care". In response, the NBA expanded their mental health guidelines by adopting new rules that required all teams to have at least one mental health professional on their full-time staff for 2019-2020 season.